Analysis of Receiving Surveillance Information System for Public Health Centre (SISPHEC.ID Application) using Technology Acceptance Model (TAM) at Kuningan District, Indonesia - Cecep Heriana (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2023)
One of the vigilance efforts against the next stage of the COVID-19 pandemic is the strengthening of surveillance information systems. The use of the Public Health Centres surveillance information system (Sisphec.id) is important in determining policies, but it needs to be tested for acceptance. The purpose of this study is to examine the use and acceptance of the Public Health Centre surveillance information system for COVID-19 with applications in Kuningan Regency. This research is a quantitative descriptive study, conducted in Kuningan Regency from October 26 to November 26, 2022. The population was 37 Public Health Centre surveillance officers and a sample of 20 respondents. Descriptive data analysis with Tableau public application and STATA 16. Result: perceived Ease of Use for applications is 85% is perceived as good, the perceived usefulness is 65% perceived as good, the social factor of users related to the application is 85% perceived, the behavioural interest variable for using the application is 90% is perceived as good, facility conditions affecting users, 90% perceived as good, usage behaviour 65% is perceived as good. The conclusion is most perceived as good for all TAM indicators namely Perceived Ease of Use, perceived usefulness, social factor variables of users, behavioural interest, and variable facility conditions affecting users and user behaviour. The recommended application sisphec.id can be used to support the Covid-19 surveillance system at Public Health Centre in Indonesia.